Bartender pours wine for a man - Unknown:::Creator::::::::::::
Photograph shows a man at a serving table acting as a bartender and pouring wine for another man at a y-Walk party. They are probably at D. B. Cooper's in San Jose. There are more bottles of wine on the table and one bottle is empty. A sign above them that reads: "Thank you Emilio Guglielmo Winery" and there are y-Walk balloons behind it.